FPGA Implementation of DTCWT and PCA Based Watermarking Technique - M. S. Sudha; T. C. Thanuja (Institute of Advanced Engineering and Science, 2018)
The hardware implementation of the image watermarking algorithm offers numerous distinct advantages over the software implementation in terms of low power consumption, less area usage and reliability. The advantages of Dual Tree Complex Wavelet Transform (DTCWT) and Principle Component Analysis (PCA) techniques are extracted to improve the robustness and perceptibility. The hardware watermarking solution is more economical, because adding the component only takes up a small dedicated area of silicon. The algorithm is developed and simulated using Matlab, Simulink and system generator. The implementation is carried out using Spartan 6 Diligent Atlys Field Programmable Gate array (FPGA). The architecture uses 256 slice registers, 257 slice Look Up Tables (LUT’s) and 47 I/O pins. It also meets the requirement of high speed architecture with a delay of 1.328ns and an operating frequency of 549.451MHz.